2017
DOI: 10.1016/j.foreco.2017.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Moose alter the rate but not the trajectory of forest canopy succession after low and high severity fire in Alaska

Abstract: Mammalian herbivory on palatable trees affects tree growth, forest composition, and forest succession. Antecedent effects of herbivores can be identified through remnants of dead stems and altered tree morphology as well as changes in tree ring patterns and growth. Increases in fire severity, particularly surface fuel combustion, in the by ten years, through repeated stunting of apical growth in aspen, without affecting the initial trajectory to an aspen-dominated canopy. Lightly burned areas, with their large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 51 publications
(83 reference statements)
4
17
0
Order By: Relevance
“…Other research in Interior Alaska suggests that intense moose browsing following fire in black spruce forests can slow but is unlikely to change the trajectory of deciduous canopy dominance in mixed stands. Our data suggest a weak positive effect of herbivory intensity on seedling densities and biomass that is consistent with optimal foraging of mammals such as moose to select more productive habitats, which also support quick recovery of seedlings from episodic browsing (Conway and Johnstone 2017, Brown et al 2018). Based on these observations, it seems unlikely that herbivory by mammals will alter the trajectory of canopy succession although there may be more subtle effects on herbivores on the timing of succession and canopy structure (Conway and Johnstone 2017).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Other research in Interior Alaska suggests that intense moose browsing following fire in black spruce forests can slow but is unlikely to change the trajectory of deciduous canopy dominance in mixed stands. Our data suggest a weak positive effect of herbivory intensity on seedling densities and biomass that is consistent with optimal foraging of mammals such as moose to select more productive habitats, which also support quick recovery of seedlings from episodic browsing (Conway and Johnstone 2017, Brown et al 2018). Based on these observations, it seems unlikely that herbivory by mammals will alter the trajectory of canopy succession although there may be more subtle effects on herbivores on the timing of succession and canopy structure (Conway and Johnstone 2017).…”
Section: Discussionsupporting
confidence: 76%
“…Our data suggest a weak positive effect of herbivory intensity on seedling densities and biomass that is consistent with optimal foraging of mammals such as moose to select more productive habitats, which also support quick recovery of seedlings from episodic browsing (Conway and Johnstone 2017, Brown et al 2018). Based on these observations, it seems unlikely that herbivory by mammals will alter the trajectory of canopy succession although there may be more subtle effects on herbivores on the timing of succession and canopy structure (Conway and Johnstone 2017). However, future changes in canopy dominance of mixed stands could still arise as a consequence of outbreaks such as that of the aspen leaf miner ( Phyllocnistis populiella ), which has had substantial impacts on deciduous trees in Interior Alaska in recent years (Wagner and Doak 2013, Boyd et al 2019).…”
Section: Discussionsupporting
confidence: 76%
“…The effects of fire on plants (e.g., Lopes and Vasconcelos, 2011;Wan et al, 2014) and the effect of plant quality on herbivore damage (e.g., Greene et al, 2012;Hahn and Orrock, 2015) have been previously documented, but the complex interaction among these processes is critical in order to understand how communities will respond to increase in fire severity. These relationships are even more complex since fire can also influence how herbivores affect plant growth (Conway and Johnstone, 2017), plant chemistry, and decomposition (Kay et al, 2008). While we connected fire severity, plant quality, and herbivore damage, other work has suggested that the soil community should also be considered.…”
Section: Discussionmentioning
confidence: 92%
“…However, the specific role of biotic and abiotic factors in post‐fire regeneration can differ substantially among fires (Ackerly, ; Camac, Williams, Wahren, Morris, & Morgan, ; Nuñez & Raffaele, ), depending on the context provided by the characteristics of the local environment. Under certain unique geographical conditions, succession cannot be completely described by a general pattern of community development, but rather is the result of a variety of dynamic site‐specific factors that change the trajectory from the typical chronosequence (Conway & Johnstone, ; Yuan et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Under certain unique geographical conditions, succession cannot be completely described by a general pattern of community development, but rather is the result of a variety of dynamic site-specific factors that change the trajectory from the typical chronosequence (Conway & Johnstone, 2017;Yuan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%